2021
DOI: 10.1111/jph.13004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and virulence spectrum of Rhizoctonia solani, the incitant of banded leaf and sheath blight of maize

Abstract: Banded leaf and sheath blight (BLSB), one of the main destructive diseases of maize worldwide, is incited by necrotrophic fungus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…A positive correlation coefficient (0.68) was found between the disease severities in relation to symptom expression. Recently, Kumar et al [23] also observed significant variation within relative lesion height with respect to isolates Rss-12 and Rsl-1 which range from 2.0 per cent to 52.6 per cent on inbreed lines (CM-600, LMDR-2, LM-12, LM-11) and hybrid (JH3459, PMH 2 and PMH 4). They also classified isolates into three groups viz., group A (highly virulent), group B (moderately virulent), group C (least virulent) based on the virulence spectrum on different cultivars.…”
Section: Pathogenicmentioning
confidence: 92%
“…A positive correlation coefficient (0.68) was found between the disease severities in relation to symptom expression. Recently, Kumar et al [23] also observed significant variation within relative lesion height with respect to isolates Rss-12 and Rsl-1 which range from 2.0 per cent to 52.6 per cent on inbreed lines (CM-600, LMDR-2, LM-12, LM-11) and hybrid (JH3459, PMH 2 and PMH 4). They also classified isolates into three groups viz., group A (highly virulent), group B (moderately virulent), group C (least virulent) based on the virulence spectrum on different cultivars.…”
Section: Pathogenicmentioning
confidence: 92%
“…A total of 14 anastomosis groups namely AG1‐ AG13 and AG BI have been reported in Rhizoctonia (Carling et al, 2002; Kumar, Kaur, & Hunjan, 2021). In India, the occurrence of BLSB has been attributed to two species of Rhizoctonia namely R. solani and R. oryzae‐sativae (Kumar, Kaur, & Hunjan, 2021), which consist primarily of anastomosis group AG1‐IA in maize and rice (Kumar, Kaur, & Hunjan, 2021; Kumar, Mehra, Kumari, Sarita, & Yadav, 2022; Singh et al, 2018). Rhizoctonia solani attacks the basal portion (lower leaf and sheath) of maize plants and induces small water‐soaked lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Anastomosis is a significant factor in Rhizoctonia species, leading to unpredictable genetic variations, virulence and posing challenges to maize growers worldwide in disease management. A total of 14 anastomosis groups namely AG1‐ AG13 and AG BI have been reported in Rhizoctonia (Carling et al, 2002; Kumar, Kaur, & Hunjan, 2021). In India, the occurrence of BLSB has been attributed to two species of Rhizoctonia namely R. solani and R. oryzae‐sativae (Kumar, Kaur, & Hunjan, 2021), which consist primarily of anastomosis group AG1‐IA in maize and rice (Kumar, Kaur, & Hunjan, 2021; Kumar, Mehra, Kumari, Sarita, & Yadav, 2022; Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%